2009
DOI: 10.1038/eye.2009.164
|View full text |Cite
|
Sign up to set email alerts
|

OCT measurements on the foveal and perifoveal retinal thickness on diabetic patients after phacoemulsification and IOL implantation

Abstract: Purpose The first aim (I.) was to measure the change of macular thickness in diabetic (DM group) and nondiabetic patients (NORMAL group), the values of operated eye (OP) were compared I.A.) to the fellow, non-operated eye (CONTROL) and I.B.) to preoperative baseline value of the operated eye (PRE). The second aim (II.) was to compare postoperative macular thickening of DM group to NORMAL group eyes. Methods Retinal thickness values of the foveal and perifoveal (fovea þ 3.0 mm, fovea þ 6.0 mm) sectors and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
0
21
1
1
Order By: Relevance
“…Several studies, including the ETDRS, did not find an association between clinically significant macular edema and cataract extraction [121,127129]. Biró and Balla measured macular thickness using optical coherence tomography (OCT) in diabetic and non-diabetic eyes following phacoemulsification and found that there was no significant difference in macular edema between the two groups [130]. Similarly, Dowler et al, failed to uncover a significant difference between ECCE and phacoemulsification vis-à-vis the progression of their patients’ macular edema or retinopathy [131].…”
Section: Lensmentioning
confidence: 99%
“…Several studies, including the ETDRS, did not find an association between clinically significant macular edema and cataract extraction [121,127129]. Biró and Balla measured macular thickness using optical coherence tomography (OCT) in diabetic and non-diabetic eyes following phacoemulsification and found that there was no significant difference in macular edema between the two groups [130]. Similarly, Dowler et al, failed to uncover a significant difference between ECCE and phacoemulsification vis-à-vis the progression of their patients’ macular edema or retinopathy [131].…”
Section: Lensmentioning
confidence: 99%
“…Kim et al showed a mean 9-μm increase in CPT at 12 weeks 21. Biró et al advocated using the 6-mm perifoveal retinal thickness for a more sensitive measure for detecting macular edema 23,24. They showed 5.3% increase in 6-mm perifoveal values at 2 months after phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Biró et al (23) compared the CFT of 18 eyes of diabetic patients with 36 eyes of nondiabetic patients using SD-OCT preoperatively and at 1, 7, 30, and 60 days post-op, with the contralateral eye acting as the control. Patients with any other ophthalmic pathologies were excluded, as well as those with severe NPDR or with proliferative DR. A significant increase was noted in the CFT in both the groups with DM and without DM as compared with their respective controls.…”
Section: Discussionmentioning
confidence: 99%